2007
DOI: 10.1111/j.1365-2559.2007.02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive markers in breast cancer – the future

Abstract: The published literature is awash with examples of new tissue biomarkers promising to predict responses to therapy in breast cancer patients. However, few, if any, of these progress from the laboratory to the clinic. In this review we discuss some of the reasons for this, illustrating our discussion with a selection of biomarkers which are in development and which may be candidates for clinical application within the next few years (topoisomerase II alpha, epidermal growth factor receptor, AKT, phosphatase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…there is no clear way to select patients that would benefit from anti-EGFR treatment in breast cancer [12]. However, post-hoc subgroup analysis of our data showed that TNBC were more likely to achieve a pCR than non-TNBC, which is in line with a previously published study [22].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…there is no clear way to select patients that would benefit from anti-EGFR treatment in breast cancer [12]. However, post-hoc subgroup analysis of our data showed that TNBC were more likely to achieve a pCR than non-TNBC, which is in line with a previously published study [22].…”
Section: Discussionsupporting
confidence: 82%
“…Whether or not, as indicated by others [12][13][14], an inverse relationship between EGFR and ER expression exists, awaits conduction of further gene expression analysis. If such an inverse relationship exists, the mechanism of action of gefitinib may be, as anticipated by others [10;11;17;18], more than simple inhibition of the EGFR tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several reasons, we focused on the importance of TOP2A. Firstly, both drugs share TOP2A as a major target and the individually variable expression level of TOP2A in breast tumors is being developed as a marker predictive for anthracycline response (9). Further, anthracyclines probably kill cancer cells by several mechanisms independent from TOP2A "poisoning."…”
Section: Introductionmentioning
confidence: 99%
“…These dysregulations confer cancerous cells with the ability to: proliferate at an increased rate; evade differentiation; develop new blood vessels (angiogenesis) within their aggregate tissues; evade death; migrate and metastasise; and resist growth inhibitory factors [5]. These hallmarks of cancer are governed at ultra-and micro-cellular levels by a complex network of signalling regulatory pathways that ultimately dictate the development, maintenance and progression of the cancer [6], as well as its histological and anatomical presentation and organisation [7]. The inherent characteristic and complex heterogeneity of the disease, governed by multivariate spatial and temporal parametric biological (pathways) and environmental (stromal) indices [8,9], make cancer extremely difficult to study and understand.…”
Section: Introductionmentioning
confidence: 99%